Characterization of BLUF-photoreceptors present in Acinetobacter nosocomialis - Abatedaga, Inés (2022)
Acinetobacter nosocomialis is a Gram-negative opportunistic pathogen, whose ability to cause disease in humans is well recognized. Blue light has been shown to modulate important physiological traits related to persistence and virulence in this microorganism. In this work, we characterized the three Blue Light sensing Using FAD (BLUF) domain-containing proteins encoded in the A. nosocomialis genome, which account for the only canonical light sensors present in this microorganism. By focusing on a light-modulated bacterial process such as motility, the temperature dependence of light regulation was studied, as well as the expression pattern and spectroscopic characteristics of the different A. nosocomialis BLUFs. Our results show that the BLUF-containing proteins AnBLUF65 and AnBLUF46 encode active photoreceptors in the light-regulatory temperature range when expressed recombinantly. In fact, AnBLUF65 is an active photoreceptor in the temperature range from 15C to 37C, while AnBLUF46 between 15C to 32C, in vitro. In vivo, only the Acinetobacter baumannii BlsA’s ortholog AnBLUF65 was expressed in A. nosocomialis cells recovered from motility plates. Moreover, complementation assays showed that AnBLUF65 is able to mediate light regulation of motility in A. baumannii ΔblsA strain at 30C, confirming its role as photoreceptor and in modulation of motility by light. Intra-protein interactions analyzed using 3D models built based on A. baumannii's BlsA photoreceptor, show that hydrophobic/aromatic intra-protein interactions may contribute to the stability of dark/light-adapted states of the studied proteins, reinforcing the previous notion on the importance of these interactions in BLUF photoreceptors. Overall, the results presented here reveal the presence of BLUF photoreceptors in A. nosocomialis with idiosyncratic characteristics respect to the previously characterized A. baumannii’s BlsA, both regarding the photoactivity temperature-dependency as well as expression patterns, contributing thus to broaden our knowledge on the BLUF family.